Saturday
March 25, 2017

Post a New Question

Posted by on .

Assume that no denominator equals 0.

sqrt12 - sqrt18 + 3sqrt50 + sqrt75

= (sqrt2^2*3) - (sqrt2*3^2) + (3sqrt2*5^2) + (sqrt3*5^2)

= (sqrt2^2*sqrt3) - (sqrt3^2*sqrt2) + (3sqrt5^2*sqrt2) + (sqrt5^2*sqrt3)

= (2*sqrt3) - (3*sqrt2) + (3sqrt5*sqrt2) + (5*sqrt3)

= 7sqrt3 + sqrt2 + sqrt5(answer)

  • Algebra II (check) - ,

    no, your roots 3's are ok, but....

    sqrt12 - sqrt18 + 3sqrt50 + sqrt75
    = √(4*3) - √(9*2) +3√(25*2) + √(25*3)
    = 2√3 - 3√2 + 15√2 + 5√3
    = 7√3 + 12√2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question